THE EFFECT OF GOVERNANCE AND SHARIA COMPLIANCE IMPLEMENTATION TOWARDS THE LEVEL OF CUSTOMER TRUST IN ISLAMIC BANK - Muhamad Dede Sulaeman; Sigid Eko Pramono; Saiful Anwar (Tazkia Islamic Finance and Business Review, 2020)
This research aims to find out how much the effect of the governance and shariacompliance implementation towards the level of customer trust in Islamic bank in Bogor. There were 159 customers of Islamic banks selected as sample. The analytical method used in this research is Structural Equation Modeling (SEM). The results presented that governance does not significantly affect the level of Islamic bank’s customer trust, while conversely sharia compliance has a significant positive effect on the level of Islamic bank’s customer trust. Thus, to increase customer trust in Islamic banks, it is necessary to improve sharia compliance.